ANALISIS PENGENDALIAN KEBISINGAN DI AREA BODY MINIBUS PERUSAHAAN KAROSERI TAHUN 2015 - Rizqa Desi Amalia; Siswi Jayanti; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
Noise is an unwanted sound. Body Mini Bus Area in Carrosserie Company has a noise level around 86,3 – 86,7 dBA.  It indicated that the noise from body minibus area has been exceeded the determined limit. It is necessary to control the noise. The aim of this research is to determine of control the noise that has done or has not been done in the area of body minibus. The researcher uses qualitative approach with interview and field observation. The subjects of this research are 3 main informants are the supervisor and the chief of body minibus area also the staff of SHE, while triangulation informants are the workers in body minibus area. Based on the research, noise control at body minibus area already using appropriate hierarchy are substitutions, engineering, administrative and personal protective equipment. However, the implementation of the hazard management is not optimal as consequences of the enormous cost and the condition of the workplace. The administrative management control has not done neither an ear health examination nor vulnerable rules and punishment for the undisciplined workers. Moreover, the worker awareness on using earplug still low. It is necessary for the supervision, upgrade the rules and punishment in relation with noise management including the use of earplug and the ear health check up periodically.